Macromolecular helicity control of poly(phenyl isocyanate)s with a single stimuli-responsive chiral switch. Issue 55 (19th June 2019) - Fukuda, Mayu; Rodríguez, Rafael; Fernández, Zulema; Nishimura, Tatsuya; Hirose, Daisuke; Watanabe, Go; Quiñoá, Emilio; Freire, Félix; Maeda, Katsuhiro
Abstract : The macromolecular helicity of poly(phenyl isocyanate)s can be tuned by a conformational switch of the chiral initiator through a domino effect. Abstract : The introduction of a single chiral substituent with a switchable conformer equilibrium at the poly(phenyl isocyanate) terminus allowed the control of the helical sense of the polymer backbone using various external stimuli. Helical sense enhancement was achieved through a domino effect, where the helical sense was assigned by VCD spectroscopy and DFT calculations.